(untitled) (International Journal of Food and Nutritional Sciences, 2019)
This research explores the rapidly developing of the two topics knows as smart buildings and smart cities, that are the results of the quick development of cutting-edge technologies. With an focus on the practical applications of advanced technologies such as Internet of Things (IoT), Building Information Modeling (BIM) and Artificial Intelligence(AI) , this research offers an in-depth review of their vital role in evolving urban environments.